answersLogoWhite

0


Best Answer

9a + 7b *remember to look and understand the letters!*

User Avatar

Ryan McKibbin

Lvl 2
โˆ™ 2021-02-08 10:07:48
This answer is:
๐Ÿ™
0
๐Ÿคจ
1
๐Ÿ˜ฎ
0
User Avatar
User Avatar

JAMIE LINDSAY

Lvl 1
โˆ™ 2021-05-11 19:19:13
what is 6a plus 3b
User Avatar

Matthew Tyler

Lvl 1
โˆ™ 2021-11-12 15:40:46
hh
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

โžก๏ธ
See all cards

Multiplication chart! :)

12 cards

2x1

2x2

2x3

2x4

โžก๏ธ
See all cards

Math and Arithmetic

20 cards

The length of a rectangular floor is 2 feet more than its width The area of the floor is 168 square feet Kim wants to use a rug in the middle of the room and leave a 2 foot border of the floor visib

The perimeter of a rectangle is 18 feet and the area of the rectangle is 20 square feet what is the width of the rectangle

The sum of two numbers is 19 and their product is 78 What is the larger number

A rectangular garden has a perimeter of 48 cm and an area of 140 sq cm What is the width of this garden

โžก๏ธ
See all cards
More answers
User Avatar

Wiki User

โˆ™ 2011-03-15 15:57:08

3a + 4b + 6a + 3b=

9a + 7b

User Avatar

User Avatar

Anonymous

Lvl 1
โˆ™ 2020-05-31 21:37:24

9a+7b

User Avatar

Add your answer:

Earn +20 pts
Q: What is 3a plus 4b plus 6a plus 3b in algebra?
Write your answer...
Submit
Related questions

What is the equivalent to 3a plus 4b - -6a - 3b?

3a + 4b - (-6a) - 3b? There is no equivalent because you did not make it an equality. However you could combine the numbers... 3a + 4b +6a -3b = 9a + 1b


What is 1a plus 2a plus 3b plus 4b and what is the answer?

1a+3b 2a+4b=3a +7b


How do you simplify 3a plus 2b - a plus 4b?

Change the order to make it more obvious: 3a - a + 2b + 4b 2a + 6b or 2 (a + 3b).


Simplify 5a plus 4b - 3a?

5a + 4b - 3a =(5a - 3a) + 4b =2a + 4b =2 (a + 2b)


What is 5a - 4b plus 2c - 3b - 6c plus a?

(5a - 4b) + (2c - 3b - 6c) + a =5a - 4b + 2c - 3b - 6c + a =(5a + a) + (-4b - 3b) + (2c - 6c) =[ 6a - 7b - 4c ].


6b plus 5a-4b plus 3a?

6b+5a-4b+3a= ? Rearrange it as 5a+3a+6b-4b = 8a+2b


What is 9a plus 3b-11a-4b?

9a + 3b - 11a - 4b = -2a -b


If the ratio of 4a to 3b is 8 to 9 what is the ratio of 3a to 4b?

1/2


What is the answer to Simplify 5a plus 4b-3a?

2a + 4b


Which expression is equivalent to (3a b)(2a - 4b)?

6a²b - 12ab²


What is 8a plus b plus 32a plus 3b?

8a+b+32a+3b=40a+4b


A plus 3b plus 5a plus 4b?

6a+7b


What is the solution of -7 plus 3b equals 4b-8?

-7+3b = 4b-8 3b-4b = -8+7 -b = -1 b = 1


-b plus 4b?

equals 3b


What is 3b plus b equal?

4b


What is 2a x 3b?

2a x 3b = 6ab


How do you simplify 3b plus b plus 6?

It is: 4b+6


What is 7 plus 4b plus 3b plus 6b plus 5?

7 + 4b + 3b + 6b + 5 =7 + 13b + 5 =12 + 13b


What is 3a plus 5b minus 6a minus 9b?

3a + 5b - 6a - 9b = -3a - 4b


5a squared plus 3b squared plus 2a squared plus 4b squared?

No


5a 2 plus 3b 2 plus 2a 2 plus 4b 2?

20a2b2


What is the simplification for 3a plus 4b-5-a plus 7b plus 3-b?

3a + 4b - 5 - 1a + 7b + 3 - 1b 2a + 10b - 5 + 3 2a + 10b - 2


3a 4b equals 7a 4b?

Clearly, there are some signs missing. So let's try the four possibilities for the second terms: 1. + and + 3a + 4b = 7a + 4b Subtract 4b from each side: 3a = 7a Subtract 3a from each side: 0 = 4a Answer : a = 0, b indeterminate (ie can have any vaue). 2. + and - 3a + 4b = 7a - 4b Subtract 4b from each side: 3a = 7a - 8b Subtract 7a from each side: -4a = -8b or 4a = 8b Answer: a = 2b 3. - and - 3a - 4b = 7a - 4b Add 4b to each side: 3a = 7a Subtract 3a from each side: 0 = 4a Answer : a = 0, b indeterminate (ie can have any vaue). 4. - and + 3a - 4b = 7a + 4b Add 4b to each side: 3a = 7a + 8b Subtract 7a from each side: -4a = 8b or 4a = -8b Answer: a = -2b Can't do better than that with the information available.


What is -6a 2b 3a-4b-5a?

It is an algabraic expession without knowing whether or not 2b and 3a are plus or minus


Negative parenthesis 3a plus 7b parenthesis minus 8a minus 4b plus 2?

Numerically, if the question looks like this:--(3a + 7b) - 8a - 4b + 2Then the answer is this:--3a - 7b - 8a - 4b + 2= -11a -11b + 2